2011
DOI: 10.1093/anatox/35.4.199
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mass Spectrometric Methods for Detection of the Anti-Protozoal Drug Imidocarb

Abstract: Imidocarb [N,N'-bis[3-(4,5-dihydro-1H-imidazol-2-yl)phenyl]urea, C(19)H(20)N(6)O(1), m.w. 348.41] is a symmetrical carbanilide derivative used to treat disease caused by protozoans of the Babesia genus. Imidocarb, however, is also considered capable of suppressing Babesia-specific immune responses, allowing Babesia-positive horses to pass a complement fixation test (CFT) without eliminating the infection. This scenario could enable Babesia-infected horses to pass CFT-based importation tests. It is imperative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…In practical operation, but m/z 175 is more plentiful and stable for greater sensitivity. Therefore, the diprotonated m/z 175 [M+2H] 2+ was finally set to the parent ion in this study, which is consistent with Lehner 's study results [29].…”
Section: Discussionsupporting
confidence: 80%
“…In practical operation, but m/z 175 is more plentiful and stable for greater sensitivity. Therefore, the diprotonated m/z 175 [M+2H] 2+ was finally set to the parent ion in this study, which is consistent with Lehner 's study results [29].…”
Section: Discussionsupporting
confidence: 80%
“…However, in our study, we found that when the ion (m/z 349.1) was used as the precursor ion, the intensity of the matrix effect was high, which seriously interfered with the detection of the sample. IMD is easily ionized in aqueous solution, and there are two main ionized forms (monoprotonated m/z 349.1 [M + H] + ; deprotonated m/z 175 [M + 2H] 2+ ) [27]. In practice, the abundance of IMD was stronger and more stable when m/z 175 was selected as the precursor ion.…”
Section: Discussionmentioning
confidence: 99%
“…To detect IM residues in animal products, scientists have developed many analytical approach, for example, high performance liquid chromatography (HPLC) (Crescenzo, et al, 2002;Park et al, 2014;Tarbin & Shearer, 1992), LC mass spectrometry (LC-MS) (Inoue et al, 2011), mass spectrophotometry (Lehner et al, 2011), and electrochemical process (Atty et al, 2020;Nezammahalleh et al, 2018). Although these analytical methods are highly sensitive and accurate, they are time consuming, costly and requiring professional operators.…”
Section: Introductionmentioning
confidence: 99%